Legal Certainty Of Investment Related Licencing In Plantation Sector - Muhammad Raza Pasaribu; Azhari Yahya (Fakultas Hukum Universitas Syiah Kuala, 2018)
According to Article 4 paragraph (2) point b the Act Number 25 of 2007 on Investment, the government has an obligation to ensure legal certainty for any investor operating in Indonesia to enhance investment climate in this country. This legal certainty needs to be ensured and provided by the government from the beginning until the end of investment process. However, the fact in Aceh Tamiang District shows that legal certainty provided by the government to foreign investor PT Simpang Kiri Plantation Indonesia is not yet in line with the above stipulation. This condition becomes the main issue that will be analyzed in this article. This research aims to analyze legal certainty provided to the investor in plantation sector in Aceh Tamiang District, and to scrutinize hindrance factors faced by PT Simpang Kiri Plantation Indonesia in conducting investment in plantation sector in this District. The method used in this research is an empirical research method. The primary data used in this article was obtained through interviewing respondents and informants. Then, library research to acquire secondary data was done by reading some literatures which are related to this topic that consists of legislations, books, goverment documents and other scholarly works. This study found that legal certainty provided by the government to PT Simpang Kiri Plantation Indonesia is relatively low. This condition can be undrestood from a long bureaucracy that must be passed by this company when they need an investment licence to proceed with their investment. In addition, there are also some hindrances faced by this company in conducting its investment in Aceh Tamiang District namely hard to get new license for new investment, and long bureaucracy process from the government to proceed with any activity designed by the company including public health service. It is recommended that the government should provide better legal certainty for investor to enhance investment climate in Aceh Province especially Aceh Tamiang District. Besides, the government is suggested to take legal action to remove any hindrance factors faced by investors to speed up investment growth in this area.